Hindrances to undergraduate student’s meaningful learning of bivariate normal distribution at Kenya university - Onyancha, Bosire Nyambane; Ogbonnaya, Ugorji I. (Universitas Papua, 2023)
The problem of the study was to investigate hindrances to undergraduate students’ meaningful learning of bivariate normal distribution (BND) in a Kenyan university. The study was informed by students’ poor performances in BND. This study adopted a case study design and a qualitative research methodology. Data was collected using a questionnaire from second- and third-year undergraduate statistics students (n=175). The data was thematically tabulated and analyzed using descriptive statistics of frequencies and percentages. The study revealed various hindrances to undergraduate students’ learning of BND, which included;- inadequate background knowledge on BND, negative attitude towards BND, lack of interest on BND, inadequate learning resources on BND, inefficiency in learning long and complex statistical equations, inability to comprehend BND function, inability to derive the conditional mean and variance equations of a joint distribution, lack of an in-depth teaching of BND, few worked examples and assignments on BND etc. It is recommended that an in-depth teaching and learning of BND coupled with adequate worked examples and assignments should be embraced by utilizing university’s freely provided internet resources to bridge students’ statistical content knowledge and pedagogical knowledge gaps.